2013
DOI: 10.1590/0037-8682-1687-2013
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological profile of Trypanosoma cruzi-infected mothers and live birth conditions in the state of Minas Gerais, Brazil

Abstract: Introduction:The aim of this study was to assess the epidemiological characteristics of Trypanosoma cruzi-infected mothers and the live birth conditions of neonates. Methods: A serological survey with IgG-specific tests was conducted using dried blood samples from newborn infants in the State of Minas Gerais. T. cruzi infection was confirmed in mothers through positive serology in two different tests, and infected mothers were required to have their infants serologically tested after the age of 6 months. The b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 9 publications
0
2
0
3
Order By: Relevance
“…Four papers on Chagas’ disease met the inclusion criteria (Brazil [GDB #1] two [ 82 , 83 ]; Argentina [GDB #3] one [ 84 ]; Colombia [GDB #5] one [ 85 ]) ( S5 Table ). Two studies represented the general population in a specific geographical area using a cross-sectional design [ 82 , 84 ], while two focussed on pregnant women (cross-sectional) [ 85 ] or women who recently gave birth (case control) [ 83 ], reflecting the importance of vertical infection transmission.…”
Section: Resultsmentioning
confidence: 99%
“…Four papers on Chagas’ disease met the inclusion criteria (Brazil [GDB #1] two [ 82 , 83 ]; Argentina [GDB #3] one [ 84 ]; Colombia [GDB #5] one [ 85 ]) ( S5 Table ). Two studies represented the general population in a specific geographical area using a cross-sectional design [ 82 , 84 ], while two focussed on pregnant women (cross-sectional) [ 85 ] or women who recently gave birth (case control) [ 83 ], reflecting the importance of vertical infection transmission.…”
Section: Resultsmentioning
confidence: 99%
“…This study also explored the relationships between serum maternal profile with low-birth and prematurity since these variables were previously reported [ 5 , 30 , 40 – 42 , 59 64 ]. A report from Moraes et al [ 65 ] showed that the prevalence of low-birth and prematurity for the region in which this study was carried out is equal to 6.5% and 9.0%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Dessa forma, duas significativas ações em saúde pública é a realização do diagnóstico precoce e terapia medicamentos eficaz no primeiro ano de vida. (PINTO et al, 2013;CARLIER et al 2015).…”
Section: Transmissão Congênitaunclassified